2012
DOI: 10.2151/sola.2012-023
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Two Adjacent Shear Lines Accompanied by Wind Gusts in the Japan Sea Coastal Region during a Cold-Air Outbreak on 12 December 2010

Abstract: Two adjacent shear lines accompanied by wind gusts exceeding 20 m s −1 passed over the Shonai region on the Japan Sea coast during a moderate cold-air outbreak on 12 December 2010. The structure of the shear lines were examined using simulation results and observational data including high-frequency upper-air soundings. Simulation results revealed that cold-airmass outflow from the Eurasian Continent had a split-flow pattern due to the blocking effect of the Changbai Mountains. One is from the south side of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…where W 3s (t ) denotes the maximum 3s mean wind speed in the previous 1 min at time t, and PreW 10m (t ) and PostW 10m (t ) are the 10min mean wind speeds just before and after the wind gust at time t, respec tively. These conditions, where the gust factor and the amounts of increase and decrease in the wind speed before and after the wind gust are much higher than the criteria of previous studies (Wakimoto 1985;Kobayashi et al 2008Kobayashi et al , 2012Kusunoki et al 2010;Tomokiyo and Maeda 2016), are schematically shown in Fig. 2.…”
Section: Definition Of Wind Gustmentioning
confidence: 60%
See 3 more Smart Citations
“…where W 3s (t ) denotes the maximum 3s mean wind speed in the previous 1 min at time t, and PreW 10m (t ) and PostW 10m (t ) are the 10min mean wind speeds just before and after the wind gust at time t, respec tively. These conditions, where the gust factor and the amounts of increase and decrease in the wind speed before and after the wind gust are much higher than the criteria of previous studies (Wakimoto 1985;Kobayashi et al 2008Kobayashi et al , 2012Kusunoki et al 2010;Tomokiyo and Maeda 2016), are schematically shown in Fig. 2.…”
Section: Definition Of Wind Gustmentioning
confidence: 60%
“…This is the first study in which detailed data from a lot of observatories distributed all over Japan are statistical ly analyzed for such a long period. This study does not focus on particular phenomena, such as tornadoes and downbursts, which cause wind gusts, unlike the previous studies (Wakimoto 1985;Kobayashi et al 2008Kobayashi et al , 2012Kusunoki 2010). The understanding of statistical characteristics of wind gusts is very import ant for science and mitigation of windrelated disas ters.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…As part of “The Shonai Area Railroad Weather Project” [ Kusunoki et al ., ; Inoue et al ., ; Mashiko , ; Nishihashi , ; Kato et al ., ], winter tornadoes and misovortices have been observed in the Japan Sea coastal region since 2007, mainly using two X band Doppler radars and a network of automated surface weather stations. These vortices can be roughly characterized by winds with V t ≈ c , where V t is the tangential wind speed and c is the translational speed of the vortex, resulting from a modest value of V t and a high value of c associated with the winter monsoon [e.g., Inoue et al ., ].…”
Section: Introductionmentioning
confidence: 99%